2019
DOI: 10.1111/nph.15988
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary origin of O‐acetyltransferases responsible for glucomannan acetylation in land plants

Abstract: Summary Mannans are an abundant cell wall polysaccharide in bryophytes, seedless vascular plants and gymnosperms. A previous study has shown that mannan acetylation in Arabidopsis and konjac is mediated by mannan O‐acetyltransferases belonging to the Domain of Unknown Function (DUF) 231 family. However, little is known about the acetylation patterns of mannans in bryophytes and seedless vascular plants, and the evolutionary origin of mannan O‐acetyltransferases in land plants has not yet been studied. Phylog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 66 publications
(133 reference statements)
0
16
0
Order By: Relevance
“…More than 1100 members of the GDSL family are reported so far from twelve different fully sequenced plant genomes [ 76 ]. The specific role of GDSL lipases/esterases in xylan deacetylation was reported by [ 63 , 77 ]. A study of the rice ( Oryza sativa ) brittle leaf sheath1 ( bs1 ) mutant revealed that it has a defect in Golgi localization of the GDSL esterase and thus confirms the role of GDSL esterase in xylan acetylation.…”
Section: Mechanism Of Deacetylationmentioning
confidence: 97%
See 2 more Smart Citations
“…More than 1100 members of the GDSL family are reported so far from twelve different fully sequenced plant genomes [ 76 ]. The specific role of GDSL lipases/esterases in xylan deacetylation was reported by [ 63 , 77 ]. A study of the rice ( Oryza sativa ) brittle leaf sheath1 ( bs1 ) mutant revealed that it has a defect in Golgi localization of the GDSL esterase and thus confirms the role of GDSL esterase in xylan acetylation.…”
Section: Mechanism Of Deacetylationmentioning
confidence: 97%
“…The degree of xylan acetylation is regulated by a Golgi-localized BS1 (BRITTLE LEAF SHEATH1) protein as the BS1 mutant lacks specific xylan acetylation patterns [ 62 ]. The search for BS1 orthologues in plants is on its way to understand occurrence and mechanisms of xylan deacetylation in the Golgi [ 63 ].…”
Section: Mechanism Of Xylan Acetylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these polymers, HMs have the simplest structures since they can be found as linear β-1,4-linked mannans (defined as containing > 90% mannose, Man), or as glucomannans that also contain β-1,4-linked glucose (Glc) units [ 8 ]. (Gluco)mannans can be decorated with galactose side chains [ 9 , 10 ] or O -acetylated [ 11 , 12 ], which increases their solubility [ 13 ]. HM is abundant in the endosperms of most legume seeds [ 14 ], and to a lesser extent in cereal grains [ 15 ], which confer important physiological properties, such as stabilizing the extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Of these polymers, HMs have the simplest structures since they can be found as linear β-1,4-linked mannans (defined as containing >90% mannose, Man), or as glucomannans that also contain β-1,4-linked glucose (Glc) units [8]. (Gluco)mannans can be decorated with galactose side chains [9,10] or O -acetylated [11,12], which increases their solubility [13]. HM is abundant in the endosperms of most legume seeds [14], and to a lesser extent in cereal grains [15], which confer important physiological properties, such as stabilizing the extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%